(3GdMhGQ GdCOHj Mhd GdTYQs (3bVGjGg GdehVhYjI, h OdGdGJg GdacQjI, h BKGQg GdafjI ef HOGjI GdbQf GdYTQjf Edi bjGe GdMQH GdYGdejI GdKGfjIs - (3CHh GdCfhGQ, eMeOs ((3GdbGgQIs (3ecJHI GdBOGHs, 2007)
(3jYO gPG GdcJGH YdGeI aGQbI ai GdOQGSGJ GdGOHjI GdeYGUQI, hgh jDQN h jMdd bVGjG GdMhGQ h GdYQGc GdGOHi GdJi CKeQJ GdfgVI GdCOHjI HeUQ ai hGbYgG GdNGU h GdYGe(B. (3ef NdGd UdGJgG HGdYGde GdYQHi, h GdJCKjQGJ GdChQHjI GdJi HGTQJ aYdgG ai GdKbGaI GdYQHjI YGekI hGdeUQjI NGUkIs
(3HHdjhLQGajI (B: (3U(B. 649-666s
3
Keywords: (3GdTYQ GdYQHis -- (3JGQjN h fbOs -- (3GdYUQ GdMOjKs; (3GdTYQ GdYQHis -- (3JGQjN h fbOs